2020
DOI: 10.1177/0309133320956567
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost electronic sensors for environmental research: Pitfalls and opportunities

Abstract: Repeat observations underpin our understanding of environmental processes, but financial constraints often limit scientists’ ability to deploy dense networks of conventional commercial instrumentation. Rapid growth in the Internet-Of-Things (IoT) and the maker movement is paving the way for low-cost electronic sensors to transform global environmental monitoring. Accessible and inexpensive sensor construction is also fostering exciting opportunities for citizen science and participatory research. Drawing on 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 91 publications
(112 reference statements)
0
42
0
Order By: Relevance
“…The majority of existing environmental applications are based on proprietary conventional commercial WSN apparatuses. Furthermore, there is a global shortage of low-cost, longrange wireless monitoring systems for measuring water table depths [36]. To date, no studies have reported on the use of LoRa-based, low-cost WSN in groundwater table management in Tanzania.…”
Section: A Primer On Lora Radio Technologymentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of existing environmental applications are based on proprietary conventional commercial WSN apparatuses. Furthermore, there is a global shortage of low-cost, longrange wireless monitoring systems for measuring water table depths [36]. To date, no studies have reported on the use of LoRa-based, low-cost WSN in groundwater table management in Tanzania.…”
Section: A Primer On Lora Radio Technologymentioning
confidence: 99%
“…The system consists of a proprietary data collection unit and an open-source data handling and visualization web application. Furthermore, Chan et al [36] proposed a groundwater observatory model that includes a low-cost probe made with low-cost pressure sensors (NXP MPX5010DP and MS5803-02ba) to measure water table depths. The submersible sensor is housed in a waterproof (aluminum tube) enclosure and a common logger in a separate open to air enclosure sample atmospheric pressure.…”
Section: B Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…With data transmission via high-gain antennae (e.g. Carvallo et al, 2017) or satellite internet, we hypothesise that low-cost sensors, embedded within an AI framework, could revolutionise mountain glacier monitoring, as it has done in many other geoscience disciplines (Chan et al, 2020). For example, such sensors could include Arduinos or Raspberry Pis (Vujovic and Maksimovic, 2014) that could act as a webcam, capture infrared images at night, detect thermal signatures, record acoustic events, detect ground displacement or tremors from calving, track velocity with GPS, or communicate with satellites for real-time ground-truthing.…”
Section: Artificial Intelligence and Machine Learningmentioning
confidence: 99%